High SARS-CoV-2 infection rates and viral loads in community-dwelling individuals from rural indigenous and mestizo communities from the Andes during the first wave of the COVID-19 pandemic in Ecuador - Morales-Jadán, Diana; Vallejo-Janeta, Alexander Paolo; Bastidas, Vanessa; Paredes-Espinosa, Maria Belen; Freire-Paspuel, Byron; Rivera-Olivero, Ismar; Ortiz-Prado, Esteban; Henriquez-Trujillo, Aquiles Rodrigo; Lozada, Tannya; , The UDLA COVID-19 Team; Garcia-Bereguiain, Miguel Angel; Jaramillo, Tatiana; et al. (Frontiers in Medicine, 2023)
Background. Neglected indigenous groups and underserved rural populations in Latin America are highly vulnerable to COVID-19 due to a poor health infrastructure and limited access to SARS-CoV-2 diagnosis. The Andean Region in Ecuador includes a large number of isolated rural mestizo and indigenous communities living under poverty conditions. Objective. We herein present a retrospective analysis of the surveillance SARS-CoV-2 testing in community dwelling population from four provinces in the Ecuadorian Andes, carried out during the first weeks after the national lockdown was lifted in June 2020. Results. A total number of 1,021 people were tested for SARS-CoV-2 by RT-qPCR, resulting in an overall infection rate of 26.2%, over 50% in several communities. Interestingly, community dwelling super spreaders with viral loads over 108 copies/mL represented 7.46% of the SARS-CoV-2 infected population. Conclusion. These results support that COVID-19 community transmission in rural communities from the Andean region was happening at the early stages of COVID-19 pandemic in Ecuador and point out the weakness of the COVID-19 control program.